Strategi Pemasaran dan Diversifikasi Produk Terhadap Volume Penjualan Buah Nanas (Studi Kasus pada Petani UMKM di Desa Tangkit Baru Kabupaten Muaro Jambi Provinsi Jambi) - Evi Fauzani (CITRA EKONOMI, 2021)
This study aims to determine and analyze the effect of marketing, and product diversification on the sales volume of pineapple (a case study on MSME farmers in Tangkit Baru Village, Muara Jambi Regency, Jambi Province). The types of data used are primary and secondary data. Data collection is done by means of questionnaires and documentation. The population of this study is the farmers who are the perpetrators of Micro, Small and Medium Enterprises (MSMEs) with a population of 13 home industries. This research method is quantitative research. The sampling technique used was the saturated sampling method, where the entire population was sampled. The results showed that: (1) the marketing mix strategy has a positive effect on sales volume; (2) there is a significant and positive effect of product diversification on sales volume; (3) and there is a significant effect between the marketing mix, product diversification together on the sales volume of pineapples.